FLUORESCENCE AND RED SHIFT OF THE PHOTOPHYSICAL PROPERTIES FROM PROTONATED SMALL MOLECULE - Zakarias Seba Ngara (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2020)
In this work, the fluorescence (FL) and bathochromic of the photophysical properties from protonated small molecule in cast film state have been investigated. To realize these purposes, the material of 4’,4’’’’-(1,4-phenylene bis (2,2’:6’,2”-terpyridine) (Phtpy) as a small molecule and camphorsulfonic acid (CSA) as an acid for protonation was selected. For Phtpy, its maxima absorption is 300 nm and no FL color emission. After CSA solution was added in chlorofom solution of Phtpy, the absorption spectrum of protonated Phtpy is broaden to longer wavelength with two new peaks appear at around 350 and 370 nm. Upon direct excitation at wavelength of 300 nm, the range of FL spectrum of original and protonated Phtpy is from 320 to 580 nm and from 370 to 580 with their maxima FL intensities at 360 and 460 nm. Interestingly, protonated Phtpy emits blue FL color emission. In addition, energy gap of protonated Phtpy is smaller than that of pristine Phtpy. Finally, the FL and remarkable red shift of absorption and FL spectra of protonated Phtpy will pave the way to develop sensor and other photonic devices with high performances in the ultaviolet region.